2017
DOI: 10.1111/jwas.12474
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid Levels Affect the Growth Performance, Lipid Deposition, and Antioxidative Capacity of Juvenile Scaleless Carp, Gymnocypris przewalskii, on the Qinghai‐Tibetan Plateau

Abstract: A 56‐d growth trial was conducted to evaluate the growth performance, lipid deposition, and antioxidative capacity of juvenile scaleless carp, Gymnocypris przewalskii, on Qinghai‐Tibetan Plateau. One‐year‐old juveniles (initial weight: 15.99 ± 0.02 g) were fed practical diets with different lipid levels of 4, 5.5, 7, 8.5, and 10%, respectively. Results showed that the best specific growth rate (SGR), feed conversion rate, and total antioxidative capacity (T‐AOC) in hepatopancreas were observed in fish fed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Therefore, a lower dietary lipid concentration may be necessary to meet the energy requirements for growth when zebrafish are fed until apparent satiety. Moreover, the results obtained in this study align with those obtained for other species in the Cyprinidae family, such as grass carp (Ctenopharyngodon idella) [27,28] , catla (Catla catla) with 8% CL [29] and scaleless carp Gymnocypris przewalskii with 7.35% CL [21]. Conversely, crucian carp (Carassius auratus var.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, a lower dietary lipid concentration may be necessary to meet the energy requirements for growth when zebrafish are fed until apparent satiety. Moreover, the results obtained in this study align with those obtained for other species in the Cyprinidae family, such as grass carp (Ctenopharyngodon idella) [27,28] , catla (Catla catla) with 8% CL [29] and scaleless carp Gymnocypris przewalskii with 7.35% CL [21]. Conversely, crucian carp (Carassius auratus var.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, fish fed 4.87 and 13.94% CL showing intermediary ingestion of feed between unsupplemented and supplemented lipid diets. Meng et al [21] also observed a significant difference in feed intake when scaleless carp were fed diets with the lowest (4% CL) and highest (10% CL) lipid levels. However, similar feed intake (P>0.05) was reported by the same authors for fish fed 5.5, 7.0, and 8.5% crude lipid in the diet.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study found that the growth reaction increased with the increase of dietary lipid level until the optimal demand level was reached, and after that it decreased as the lipid level in the diet increased ( Meng et al., 2018 ). In the present study, HFD significantly decreased the SGR and the SR of juvenile grass carp and increased the FCR compared with the regular diet, indicating the adverse effects of excessive fat intake.…”
Section: Discussionmentioning
confidence: 99%
“…The indicators for evaluating a healthy intestine include goblet cell count, intestinal villus height (VH), villus width (VW) and so on ( Kuebutornye et al., 2020 ). Many studies have reported that HFD decreased the health status of the intestine ( Ding et al., 2010 ; Meng et al., 2018 ). The present study also observed that the intestine of juvenile grass carp fed with HFD showed structural disorder and a decrease in VH and VW, which might consequently result in the increase of the FCR.…”
Section: Discussionmentioning
confidence: 99%